The Rift: A New Africa Breaks Free - Pásztor, Szabolcs (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Pásztor Szabolcs Alex Perry The Rift: A New Africa Breaks Free című könyvét mutatta be.